Itraconazole Side Chain Analogues: Structure–Activity Relationship Studies for Inhibition of Endothelial Cell Proliferation, Vascular Endothelial Growth Factor Receptor 2 (VEGFR2) Glycosylation, and Hedgehog Signaling - Shi, Wei (2011)
[Image: see text] Itraconazole is an antifungal drug that was recently found to possess potent antiangiogenic activity and anti-hedgehog (Hh) pathway activity. To search for analogues of itraconazole with greater potency and to understand the structure–activity relationship in both antiangiogenic and Hh targeting activity, 25 itraconazole side chain analogues were synthesized and assayed for inhibition of endothelial cell proliferation and Gli1 transcription in a medulloblastoma (MB) culture. Through this analysis, we have identified analogues with increased potency for inhibiting endothelial cell proliferation and the Hh pathway, as well as VEGFR2 glycosylation that was recently found to be inhibited by itraconazole. An SAR analysis of these activities revealed that potent activity of the analogues against VEGFR2 glycosylation was generally driven by side chains of at least four carbons in composition with branching at the α or β position. SAR trends for targeting the Hh pathway were divergent from those related to HUVEC proliferation or VEGFR2 glycosylation. These results also suggest that modification of the sec-butyl side chain can lead to enhancement of the biological activity of itraconazole.